Regenerasi Jaringan pada Ikan Kerapu Cantang (Epinephelus fuscoguttatus lanceolatus) yang Terpapar Limbah Deterjen Melalui Perendaman Ekstrak Padina australis dengan Dosis Berbeda - Farah Diba Sani; Marcelien Dj. Ratoe Oedjoe; Ade Yulita Hesti Lukas (Journal of Marine and Aquatic Sciences, 2022)
Padina australis has bioactive compounds as antimicrobials in the form of phenols and their derivatives (flavonoids) which can inhibit the growth of bacteria that interfere with the function of the cytoplasmic membrane and can prevent spoilage and damage by microorganisms. This research was conducted from October to November 2022 at the Faculty of Animal Husbandry, Maritime Affairs and Fisheries, Nusa Cendana University, Kupang. The purpose of this study was to determine how many doses of Padina australis were effective in treating skin, gill and liver tissue damage of cantang grouper (Epinephelus fuscoguttatus lanceolatus) exposed to detergent. The method used is an experiment with a completely randomized design (CRD) with 3 treatments and 3 replications. The treatments used were control without detergent and Padina australis, 0.25g/l detergent and treatment with Padina australis with doses of 0.5%, 1% and 1.5%. The fish used was grouper cantang (Epinephelus fuscoguttatus lanceolatus) with a size of 8-9 cm. Treatment was done by soaking the fish for 10 minutes with the extract for 3 consecutive days. The fish were then fixed with 95% alcohol solution for further histology. The results showed that the administration of Padina autralis effect on changes in the histology of the skin, gill, and liver of cantang grouper. Changes that occur in the skin in the form of degeneration of vacuoles, in the gill lamellae hemorrhage occurs and the liver undergoes vacuole degeneration and necrosis. The best dose is found in the 1.5% treatment but it has not been effective in treating liver tissue.